Analisis dan Desain Struktur Atas Hotel 10 Lantai di Kabupaten Bogor terhadap Beban Gempa: Analysis and Design of the Top Structure of a 10 Floor Hotel in Bogor Regency Against Earthquake Loads - I Wayan Wirya Aristyana; Fauzan, Muhammad (Jurnal Teknik Sipil dan Lingkungan, 2021)
The type of soil at the location of the hotel building is a type of medium land (D). The applications used in this study are ETABS V16.1 and AutoCAD. Based on the PUSKIM website, the Ss and S1 Bogor City were 0.881 and 0.356, respectively. Based on the results of the analysis of the application ETABS V16.1 obtained fewer reinforcement design results than the existing reinforcement. The maximum nominal moment of the beam is 508.3 kNm while the ultimate moment is 498.4 kNm. The maximum nominal shear force of the beam is 565.9 kN while the ultimate shear force is 538.4 kN. The maximum nominal moment of the column is 1488.5 kNm while the maximum ultimate moment is 1478 kNm. The maximum nominal axial force of the column is 6291 kN while the maximum ultimate axial force is 6287 kN. The maximum nominal bending moment of the floor plate is 41.3 kNm while the maximum ultimate moment is 39.9 kNm. The maximum nominal shear force of the floor plate is 234.7 kN while the maximum ultimate shear force is 228.9 kN. The nominal shear force of shear wall is 8238.5 kN while the ultimate shear force is 8194.7 kN. Based on the internal forces, the building that has been built is in accordance with the plan so that it is safe to withstand earthquake loads.